2019
DOI: 10.1167/19.12.2
|View full text |Cite
|
Sign up to set email alerts
|

Been there, seen that, done that: Modification of visual exploration across repeated exposures

Abstract: The underlying factors that determine gaze position are a central topic in visual cognitive research. Traditionally, studies emphasized the interaction between the lowlevel properties of an image and gaze position. Later studies examined the influence of the semantic properties of an image. These studies explored gaze behavior during a single presentation, thus ignoring the impact of familiarity. Sparse evidence suggested that across repetitive exposures, gaze exploration attenuates but the correlation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Overall, the previous study ( Lancry-Dayan et al, 2019 ) reported a similar pattern of results in all experiments: as the images became more familiar across repetitive exposures, the mean fixation duration increased significantly. In the second and third experiments, these findings were only observed for the repeated images (and not for the novel images that changed on each block), thus strengthening the claim that familiarity is likely to be the cause of the prolonged fixations.…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…Overall, the previous study ( Lancry-Dayan et al, 2019 ) reported a similar pattern of results in all experiments: as the images became more familiar across repetitive exposures, the mean fixation duration increased significantly. In the second and third experiments, these findings were only observed for the repeated images (and not for the novel images that changed on each block), thus strengthening the claim that familiarity is likely to be the cause of the prolonged fixations.…”
Section: Methodssupporting
confidence: 71%
“…This dataset comprised three experiments. The first two experiments have been published elsewhere (Lancry-Dayan, Kupershmidt, & Pertzov, 2019). Note that the original study included another experiment that was excluded here because of a problem in its design (also reported in the original article).…”
Section: Dataset 3: Repetitive Displaysmentioning
confidence: 99%
“…In fact, there is evidence suggesting that previous experiences might influence visual exploration, including the number of fixations ( Sharot et al. 2008 ; Hannula 2010 ; Wolfe and Horowitz 2017 ; Lancry-Dayan et al. 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Second, to confirm that the described effects are not driven by the location of the familiar object on the screen, we decided to present each object four times in the parallel display, once in each location. While this feature can be justified in light of counterbalancing considerations, previous studies suggest that repetition may also influence the viewing patterns (Althoff & Cohen, 1999;Lancry-Dayan et al, 2019;Ryan et al, 2000). To overcome this issue, we analyzed only trials in which the familiar object has appeared for the first time (see the online supplementary materials).…”
Section: Discussionmentioning
confidence: 99%
“…The repetitive presentation of objects across the experiment was designed to control for possible artifacts (e.g., the location on the screen in the parallel display). However, these repetitions could also modify different aspects of gaze behavior (Althoff & Cohen, 1999;Lancry-Dayan et al, 2019;Ryan et al, 2000). To rule out such possibility, we report in the online supplementary materials an analysis conducted only on the first repetition of the familiar object.…”
Section: Stimulimentioning
confidence: 99%